Dark Tourism and Ethical Heritage Development in Indonesia - Citra Maharani Dewi (Bali Tourism Journal, 2026)
Dark tourism has emerged as one of the fastest-growing forms of special interest tourism in the contemporary tourism industry. This phenomenon refers to visits to places associated with death, tragedy, disaster, war, and human suffering. In Indonesia, dark tourism has developed through destinations such as Trunyan Village in Bali, the Bali Bombing Memorial, the Aceh Tsunami Museum, Lubang Buaya Museum, and Lawang Sewu in Semarang. This study aims to analyze the development of dark tourism in Indonesia and examine the ethical challenges surrounding the commercialization of tragedy and historical memory. Using a qualitative descriptive approach, data were collected through literature review and document analysis from tourism studies, media reports, and previous academic publications. The findings reveal that dark tourism in Indonesia possesses significant educational, cultural, and economic potential, particularly in strengthening historical awareness and preserving collective memory. However, the increasing commercialization of mystical narratives, horror attractions, and sensational promotion has created ethical dilemmas, including distortion of historical facts, commodification of suffering, and reduction of educational value. In destinations such as Lawang Sewu, mystical branding often overshadows its historical significance as a colonial heritage site and symbol of anti-colonial struggle. Similarly, Trunyan Village demonstrates how indigenous funeral traditions can attract tourists while simultaneously risking cultural exploitation if not managed responsibly. This study concludes that sustainable dark tourism development requires ethical management, community participation, culturally sensitive interpretation, and balanced storytelling that prioritizes education and remembrance over sensationalism. Through appropriate governance, dark tourism can function not only as an economic resource but also as a medium for cultural reflection, historical learning, and intercultural understanding.